Green logistics adoption and operational performance within the road freight sector: The moderating role of management commitment - James Kanyepe; Mikel Alfaneta; B. Zizhou (Logistics Research, 2023)
The road freight sector plays a pivotal role in economic development as it facilitates the movement of physical flows in both domestic and international supply chains. However, its significant contribution to greenhouse gas (GHG) emissions has made it a major contributor to climate change. Despite urgent calls for green logistics initiatives to mitigate these effects, adoption rates remain low, especially in developing countries. This study investigates how the adoption of green logistics practices can influence the operational performance of firms in the Zimbabwean Road freight sector. This study also explores the moderating role of management commitment in the relationship between the adoption of green logistics practices and operational performance. To achieve this, an explanatory survey was conducted with 184 employees from randomly selected companies in the road freight sector. The findings reveal that the adoption of green logistics practices positively influences operational performance. In addition, this study found that management commitment moderated this relationship. It is worth noting that this study represents the first study that examines the effect of adopting green logistics on operational performance in Zimbabwe, thus providing a novel contribution to the logistics literature. Additionally, it extends the knowledge on green logistics adoption within the sub-Saharan region and other developing parts of the world. Furthermore, this study recommends that policymakers collaborate with key stakeholders to accelerate the adoption of green logistics practices and embrace modern technologies to reduce greenhouse gas emissions.
Keywords: 650; Greenhouse Gas Emissions; Green Logistics; Operational Performance; Road Freight Transport; Sub-Saharan region